Organic Manure Improves Soybean Response to Rhizobia Inoculant and P-Fertilizer in Northern Ghana - ULZEN, Jacob; Abaidoo, Robert C.; Ewusi-Mensah, Nana; Osei, Ophelia; Masso, Cargele; Opoku, Andrews (Frontiers in Agronomy, 2020)
Inherently low concentrations of soil nutrients and erratic rainfall pattern in sub-Sahara Africa limit soybean response to rhizobia inoculant and P-fertilizer. The study was conducted to: (i) improve soybean response to rhizobia inoculation and P-fertilizer through the addition of organic manure; (ii) enhance rain water use efficiency and (iii) determine the economic viability of combined application of the three factors in soybean cropping systems in the Northern region of Ghana. A factorial experiment with two levels of rhizobia inoculant, two levels of Phosphorus, two different kinds organic manure [fertisoil (a commercially prepared compost from urban waste, rice husks, of poultry manure and shea butter waste) and cattle manure] and a control arranged in randomized complete block design with three replications was established on farmers' fields. The combined application of rhizobia inoculant, P-fertilizer, and organic manure markedly increased nodulation, shoot biomass, haulms, harvest index (HI), P agronomic efficiency (P-AE), and rain water use efficiency (RUE) compared to the control. The combined application of rhizobia inoculant, P-fertilizer, and fertisoil increased grain yield by four-folds whereas the combined application of rhizobia inoculant, P-fertilizer, and cattle manure increased grain yield by three- folds. Harvest index, P-AE, and RUE were relatively higher with the fertisoil treatment combinations than with the cattle manure combinations and the control treatment. The application of rhizobia inoculant, P-fertilizer in combination with fertisoil was profitable with VCR of 2 as compared to the combination of cattle manure which had a VCR of 0.40. The results showed that fertisoil offers a better option of improving soybean response to rhizobia inoculant and P-fertilizer; and has the potential to enhance rain water use efficiency. However, the long term benefit must be quantified.